2017
DOI: 10.1186/s12902-017-0176-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of calf circumference with insulin resistance and non-alcohol fatty liver disease: the REACTION study

Abstract: BackgroundThe feature of nonalcoholic fatty liver disease (NAFLD) is pathological excessive liver lipid accumulation of subjects who without history of alcohol abuse. Calf circumference is a proxy for lower-body fat and screening method for the identification of subjects with acatastatic lipid accumulation. The objective of this study was to examine the association between calf circumference and NAFLD.MethodsThe study was a cross-sectional analysis including 8850 middle-aged and elderly individuals. NAFLD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
(41 reference statements)
3
8
1
Order By: Relevance
“…Thus, this factor might increase the risk of NAFLD and justify our results. Contrary to the results of previous studies on the significant effect of 2-h glucose on NAFLD (38), this study failed to show a statistically significant relationship between 2-h glucose and NAFLD. The possible reason for this finding could be the small number of subjects with abnormal 2-h glucose in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, this factor might increase the risk of NAFLD and justify our results. Contrary to the results of previous studies on the significant effect of 2-h glucose on NAFLD (38), this study failed to show a statistically significant relationship between 2-h glucose and NAFLD. The possible reason for this finding could be the small number of subjects with abnormal 2-h glucose in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are consistent with the evidence in the current literature, since it has been shown that calf circumference tends to decrease as age advances (Gonzalez et al, 2021). In fact, evidence has shown that conditions such as sarcopenia, disability, and chronic noncommunicable diseases have a close relationship with calf circumference (Zhang et al, 2017). Furthermore, this parameter could predict nutritional risks, frailty, and predict mortality in the older adults (Wei et al, 2022) In summary, the monitoring and control of some anthropometric parameters such as the measurement of the circumferences of the limbs, is a simple, practical, and important way of evaluating the health of the older adults in the community context.…”
Section: Anthropometric Parameterssupporting
confidence: 92%
“…The Global NAFLD Registry data on clinical and patient‐reported outcomes showed that NAFLD patients in South Asia were the youngest, and had the highest employment rates and the lowest rates of MetS 6 . Calf circumference, neck circumference, chronic kidney disease, and impaired lung function were found to be associated with NAFLD in our community‐based study in adults in Shanghai, China 7–10 …”
Section: Risk Factors For and Natural History Of Nafld In Asiamentioning
confidence: 70%
“…6 Calf circumference, neck circumference, chronic kidney disease, and impaired lung function were found to be associated with NAFLD in our community-based study in adults in Shanghai, China. [7][8][9][10] According to the GO ASIA initiative study, the percentages of NASH and advanced fibrosis were 62.9% and 17.2% among 1008 patients with biopsy-proven NAFLD. 11 The proportion of advanced fibrosis in patients with NASH was higher than that in those with SFL (20.7% vs 11.2%).…”
Section: Risk Factors For and Natural History Of Nafld In Asiamentioning
confidence: 99%